STUDY OF FIXED DOSE COMBINATIONS IN A TERTIARY CARE HOSPITAL - Pisal, Shaunak A; Jadhav, Sujata A; Khanwelkar, Chitra C; Thorat, Vandana M; Matule, Somnath M (Asian Journal of Pharmaceutical and Clinical Research, 2016)
ABSTRACT Objective: To study and analyze the pattern of fixed dose combinations (FDCs) in medicine outpatient clinic. Methods: The study is prospective cross-sectional study was conducted for 2 months in medicine outpatient clinic in tertiary care hospital. After taking approval from Institutional Ethics Committee, the data were collected on every working day of the hospital. Prescriptions from the patients coming to medicine outpatient clinic outpatient department were taken and required information is filled in data record form. Results: A total of 83 prescriptions were included in the study. Out of 287 drugs, 111, i.e., 39.92% were fixed dose formulations. As per drug category analysis, nutritional supplements were used (47.74%). While 27.02% and 9.03% of FDCs were given for cardiovascular complains and respiratory complains, respectively. FDCs used for other conditions were 16.21%. About 29.72% of total FDCs are included in approved list of FDCs by Drugs Controller General of India (DCGI), November 2014. Conclusion: 39.92% drugs are FDCs out of total prescribed drugs. Nutritional supplements are prescribed in higher concentrations. Out of total FDCs only 29.72% were included in DCGI approved list of FDCs and only four FDCs are found in the WHO list of essential drugs. Keywords: Fixed dose combinations, Prescriptions, Approved, Drugs Controller General of India.